Teaching English in Inclusive Primary School: Teachers’ Challenges and Coping Strategies - Shilvani, Shilvani; Yohanes Gatot Sutapa Yuliana; Clarry Sada (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
This research investigated the teachers' challenges and coping strategies in teaching English in ZonaKata Inclusive Primary School in the academic year 2022/2023. This research was designed as qualitative case-study research to discover teachers' challenges and coping strategies when teaching English in inclusive settings. Five teachers who teach grades one through five at ZonaKata Inclusive Primary School participated in the study. The observation, interviews, and a review of the documents showed that the students' emotional-behavioral problems and communication-language features problems are the teacher's challenges during English teaching-learning. Therefore, the coping strategies that the teachers used were through developing and maintaining a good relationship with the students, differentiation (content, process, and product) to accommodate the different needs of the students, and collaboration between teachers in teaching. In short, the combination of these strategies effectively dealt with challenges and is recommended for teaching English in inclusive schools.